Systematic review with meta-analysis: the risk of mother-to-child transmission of hepatitis B virus infection in sub-Saharan Africa - (:unkn) unknown (My University, 2016)
Background: The risk of mother-to-child transmission of hepatitis B virus (HBV) has been quoted as 70-90% among women positive for hepatitis B surface antigen (HBsAg) and e antigen (HBeAg), and 5-30% among HBsAg-positive HBeAg-negative women. These risks are derived from Asia; little is known about sub-Saharan Africa.Aim: To determine the risk of mother-to-child transmission in sub-Saharan Africa, according to maternal HBeAg and type of prophylaxis.Methods: We searched Medline, Global Health, Embase, African Journals Online and African Index Medicus. We included observational or interventional studies that enrolled infants of HBV-infected women, and that tested for HBsAg or HBV DNA between 3 and 12 months of age.Results: Fifteen articles from 11 African countries were included. Among HBeAg-positive women, the pooled risk was 38.3% (95% CI: 7.0-74.4%) without prophylaxis, which was significantly lower than the lower bound of 70-90% risk in the literature (P = 0.007). Among HBeAg-negative women, the pooled risk was 4.8% (95% CI: 0.1-13.3%) without prophylaxis, which lays within the lower range of the 5-30% risk in Asia. By extrapolating the pooled transmission risks to the number of births to infectious mothers, an estimated 1% of newborns (n = 367 250) are annually infected with HBV at birth in sub-Saharan Africa.Conclusions: Compared to Asia, the risk of mother-to-child transmission is low in sub-Saharan Africa. However, the annual number of infants perinatally infected with HBV is twice the number of incident paediatric HIV infections in sub-Saharan Africa (n = 190 000). This highlights the importance of preventing mother-to-child transmission of HBV in sub-Saharan Africa, which has been long neglected.
Keywords: African Research